Assessment of peri-implant tissues in posterior implants placed using flapless approach: A clinicoradiographic study - Pranjali Vijaykumar Bawankar; Abhay Pandurang Kolte; Rajashri Abhay Kolte (Journal of Indian Society of Periodontology)
Background: It is important to prognosticate the hard- and soft-tissue alterations in immediate and delayed implants, as inadequacy can lead to complications affecting the long-term survival of the implant. Therefore, the purpose of this study was to evaluate and compare the hard- and soft-tissue changes in immediate and delayed posterior implants with a flapless approach. Materials and Methods: With an equal allocation ratio, the study included 46 patients requiring implant treatment in the posterior segment, including the premolars and molars. Group 1 consisted of patients with immediate implants, whereas Group 2 consisted of patients who received delayed implants. The clinical parameters, including plaque index (PI), gingival index, modified sulcus bleeding index, probing depth, and soft-tissue assessment using the Testori esthetic score (TS), were evaluated at baseline, 3, 6, 9, and 12 months. Hard-tissue parameters, such as buccal bone thickness (BBT), crestal bone height (CBH), and ridge width, were evaluated radiographically with cone-beam computed tomography at baseline and 12 months posttherapy. Results: Intragroup comparisons in both the groups showed significant differences in PI, probing pocket depth, and TS over time (P = 0.00). The mean BBT at the crest in delayed implants (1.76 ± 0.24) significantly reduced after 12 months compared to immediate implants. A significantly higher TS score was observed after 12 months in both the groups. Conclusion: A significant difference in TS scores after 12 months was found between the two groups, with better esthetics in Group 1 compared to Group 2. However, no significant changes in BBT or CBH were observed after 12 months in Group 1.